Ethnic and Religious Conflicts in India: A Comprehensive Analysis - Baxter Arlen (GoAcademica Research & Publishing, 2023)
This scholarly article delves into the multifaceted nature of ethnic and religious conflicts in India, a country renowned for its diverse cultural and social tapestry. The paper explores the historical, socio-political, and economic factors that contribute to these conflicts, while also examining the implications for national stability and unity. Through an interdisciplinary approach, the study analyzes various instances of conflicts, their root causes, and potential strategies for resolution. By shedding light on the complexities of these conflicts, this article seeks to contribute to a better understanding of the challenges India faces in maintaining communal harmony and forging a path towards a more inclusive future.